Preparation method of supercritical modified boron nitride nanotube thermal conductive filler and adhesive
Through the supercritical modification of boron nitride nanotubes, the problem of boron nitride nanotubes stacking in polymers is solved, the dispersion and grafting rate of thermal fillers are improved, and the thermal conductivity is significantly improved.
Patent Information
- Application Number
- CN202311164608.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-11
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2043-09-11
AI Technical Summary
Boron nitride nanotubes are prone to accumulate in polymers, affecting thermal conductivity, and the existing surface modification methods are not effective, resulting in a decrease in dispersion and thermal conductivity of thermal fillers in adhesives.
The supercritical modification method is used to react the silane coupling agent with the boron nitride nanotube in a supercritical reactor, and the dispersion and grafting rate of the boron nitride nanotube is improved by using carbon dioxide gas protection and rapid pressure relief. This enhances thermal conductivity.
Through supercritical modification treatment, the dispersion and grafting rate of boron nitride nanotubes are improved, and the thermal conductivity of thermal fillers in adhesives is significantly improved.
Smart Images

Figure CN117264561B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method of a heat-conductive filler and an adhesive, and belongs to the technical field of adhesives. Background Art
[0002] Boron nitride is a thermally conductive filler with excellent performance, which can be used to improve the thermal conductivity of polymers. However, boron nitride nanomaterials are prone to accumulation and affect the thermal conductivity of the final polymer. Therefore, silane coupling agents are generally used to modify their surface to improve their dispersibility. The main process is to ultrasonically disperse boron nitride in isopropanol and then add it to a silane coupling agent and ethanol solution to react at around 70°C. However, due to the high chemical inertness of boron nitride nanotubes, there are very few chemically active sites on their surface, and the modification effect is extremely poor, which in turn affects the subsequent dispersion of boron nitride thermal conductive fillers in adhesives and greatly reduces the thermal conductivity effect. Summary of the invention
[0003] In view of the defects of the above-mentioned prior art, the present invention provides a method for preparing a supercritical modified boron nitride nanotube thermal conductive filler, the purpose of which is to improve the dispersibility and grafting rate of boron nitride nanotubes to further enhance the effect of improving thermal conductivity. The present invention provides a method for preparing a thermally conductive adhesive, the purpose of which is to improve the thermal conductivity of the adhesive.
[0004] The technical scheme of the present invention is: a preparation method of a supercritical modified boron nitride nanotube thermal conductive filler, comprising the steps of: adding the hydrolyzed silane coupling agent together with the boron nitride nanotube into a supercritical reactor for reaction, protecting the reaction process with carbon dioxide gas, maintaining the temperature at 30-60°C, setting the pressure at 8-30MPa, recovering the normal pressure within 5 seconds after the reaction is finished to prepare the supercritical modified boron nitride nanotube, adding the supercritical modified boron nitride nanotube into an acrylic resin solution and stirring to prepare a mixed solution, placing the mixed solution in a supercritical reactor for reaction, protecting the reaction process with carbon dioxide gas, maintaining the temperature at 20-70°C, setting the pressure at 10-40MPa, and obtaining the supercritical modified boron nitride nanotube thermal conductive filler after the reaction is finished.
[0005] Furthermore, the mass ratio of the boron nitride nanotubes to the hydrolyzate of the silane coupling agent is 1:5-30 based on the boron nitride nanotubes and the silane coupling agent.
[0006] Furthermore, the silane coupling agent is one of KH550, KH560 and KH570.
[0007] Furthermore, the boron nitride nanotube has a length of 10 to 20 μm and a diameter of 50 to 200 nm.
[0008] Furthermore, the silane coupling agent is hydrolyzed with an ethanol aqueous solution.
[0009] Furthermore, the acrylic resin solution is prepared by dissolving acrylic resin in an organic solvent, and the mass ratio of the supercritical modified boron nitride nanotubes to the acrylic resin solution in the mixed solution is 1:10-40 based on the supercritical modified boron nitride nanotubes to the acrylic resin.
[0010] Furthermore, the organic solvent is butyl acrylate solvent.
[0011] A method for preparing an adhesive comprises mixing the supercritical modified boron nitride nanotube thermal conductive filler prepared by the method for preparing the supercritical modified boron nitride nanotube thermal conductive filler into acrylic adhesive and stirring the mixture.
[0012] Furthermore, the volume fraction of the supercritical modified boron nitride nanotube thermal conductive filler in the acrylic adhesive is 15% to 40%.
[0013] Furthermore, the supercritical modified boron nitride nanotube thermal conductive filler is mixed into the acrylic adhesive and stirred at 12000-15000 r / min for 10-20 min.
[0014] Compared with the prior art, the advantages of the technical solution provided by the present invention are:
[0015] When the supercritical carbon dioxide fluid infiltrating between the boron nitride nanotubes is rapidly depressurized, the carbon dioxide fluid changes from liquid to gas and evaporates from the boron nitride nanotubes. The huge volume difference caused by the rapid volume expansion of carbon dioxide separates the entangled boron nitride nanotubes. The spacing between the aggregated boron nitride nanotubes increases, the shape becomes fluffy and dispersed, and the size of the aggregates changes from large to small, making the modified boron nitride nanotubes more dispersible.
[0016] Before mixing with the adhesive, the supercritical modified boron nitride nanotube thermal conductive filler and the acrylic acid solution are subjected to a supercritical grafting reaction in a carbon dioxide atmosphere. The carbon dioxide fluid can fully penetrate the surface of the boron nitride nanotubes, increase the effective collision between the silane coupling agent, the acrylic acid monomer and the surface of the boron nitride nanotubes, and improve the efficiency of the grafting reaction, so that more acrylic acid monomers are grafted on the surface of the boron nitride nanotubes, which is beneficial to the dispersion in the acrylic adhesive, thereby improving the thermal conductivity of the adhesive. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The thermogravimetric analysis diagram of Example 1 and unmodified pure boron nitride nanotubes.
[0018] Figure 2 This is a diagram of the dispersion state of Example 1 and unmodified pure boron nitride nanotubes in acrylic emulsion. Implementation
[0019] The present invention is further described below in conjunction with examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. After reading this description, various equivalent modifications to this description by those skilled in the art fall within the scope defined by the claims attached to this application.
[0020] Example 1: A mixed solution of anhydrous ethanol and distilled water with a mass ratio of 9:1 was prepared, and the pH was adjusted to 5 with acetic acid. 15g of silane coupling agent (KH560) was put into the mixed solution for hydrolysis for 1h. Then the mixed solution and 1g of boron nitride nanotubes with a length of 15μm and a diameter of 100nm were added to a supercritical reactor for reaction. During the reaction, carbon dioxide gas was protected, the temperature in the reactor was maintained at 40°C, the pressure was set to 20MPa, and the reaction was carried out for 2h. After the reaction was completed, the product was taken out and washed with ethanol 3 times, and dried in an oven at 60°C to obtain supercritical modified boron nitride nanotubes using silane coupling agent.
[0021] 25g of acrylic resin was dissolved in butyl acrylate solvent, and then 1g of supercritical modified boron nitride nanotubes was added. The mixture was stirred at 8000 r / min for 10 min using a high-speed stirrer. The stirred mixed solution was placed in a supercritical reactor for reaction. During the reaction, carbon dioxide gas was protected, the temperature in the reactor was maintained at 50°C, the pressure was set to 30MPa, and the reaction was carried out for 1.5h to obtain a supercritical modified boron nitride nanotube thermal conductive filler. The supercritical modified boron nitride nanotube thermal conductive filler was mixed into the acrylic adhesive at a volume fraction of 30% and stirred at a high speed of 15000r / min for 20min to obtain an adhesive.
[0022] Example 2: A mixed solution of anhydrous ethanol and distilled water with a mass ratio of 9:1 was prepared, and the pH was adjusted to 5 with acetic acid. 15g of silane coupling agent (KH560) was placed in the mixed solution for hydrolysis for 1h. Then the mixed solution and 1g of boron nitride nanotubes with a length of 15μm and a diameter of 100nm were added to a supercritical reactor for reaction. During the reaction, carbon dioxide gas was protected, the temperature in the reactor was maintained at 30°C, the pressure was set to 30MPa, and the reaction was performed for 1h. After the reaction was completed, the product was taken out and washed with ethanol 3 times, and dried in an oven at 60°C to obtain supercritical modified boron nitride nanotubes using silane coupling agent.
[0023] 25g of acrylic resin was dissolved in butyl acrylate solvent, and then 1g of supercritical modified boron nitride nanotubes was added. The mixture was stirred at 8000 r / min for 10 min using a high-speed stirrer. The stirred mixed solution was placed in a supercritical reactor for reaction. During the reaction, carbon dioxide gas was protected, the temperature in the reactor was maintained at 50°C, the pressure was set to 30MPa, and the reaction was carried out for 1.5h to obtain a supercritical modified boron nitride nanotube thermal conductive filler. The supercritical modified boron nitride nanotube thermal conductive filler was mixed into the acrylic adhesive at a volume fraction of 30% and stirred at a high speed of 15000r / min for 20min to obtain an adhesive.
[0024] Example 3, a mixed solution of anhydrous ethanol and distilled water with a mass ratio of 9:1 was prepared, and the pH was adjusted to 5 with acetic acid. 15g of silane coupling agent (KH560) was put into the mixed solution for hydrolysis for 1h. Then the mixed solution and 1g of boron nitride nanotubes with a length of 15μm and a diameter of 100nm were added to a supercritical reactor for reaction. During the reaction, carbon dioxide gas was protected, the temperature in the reactor was maintained at 60°C, the pressure was set to 8MPa, and the reaction was carried out for 3h. After the reaction was completed, the product was taken out and washed with ethanol 3 times, and dried in an oven at 60°C to obtain supercritical modified boron nitride nanotubes using silane coupling agent.
[0025] 25g of acrylic resin was dissolved in butyl acrylate solvent, and then 1g of supercritical modified boron nitride nanotubes was added. The mixture was stirred at 8000 r / min for 10 min using a high-speed stirrer. The stirred mixed solution was placed in a supercritical reactor for reaction. During the reaction, carbon dioxide gas was protected, the temperature in the reactor was maintained at 50°C, the pressure was set to 30MPa, and the reaction was carried out for 1.5h to obtain a supercritical modified boron nitride nanotube thermal conductive filler. The supercritical modified boron nitride nanotube thermal conductive filler was mixed into the acrylic adhesive at a volume fraction of 30% and stirred at a high speed of 15000r / min for 20min to obtain an adhesive.
[0026] Example 4: A mixed solution of anhydrous ethanol and distilled water with a mass ratio of 9:1 was prepared, and the pH was adjusted to 5 with acetic acid. 15g of silane coupling agent (KH560) was placed in the mixed solution for hydrolysis for 1h. Then the mixed solution and 1g of boron nitride nanotubes with a length of 15μm and a diameter of 100nm were added to a supercritical reactor for reaction. During the reaction, carbon dioxide gas was protected, the temperature in the reactor was maintained at 40°C, the pressure was set to 20MPa, and the reaction was carried out for 2h. After the reaction was completed, the product was taken out and washed with ethanol 3 times, and dried in an oven at 60°C to obtain supercritical modified boron nitride nanotubes using silane coupling agent.
[0027] 25g of acrylic resin was dissolved in butyl acrylate solvent, and then 1g of supercritical modified boron nitride nanotubes was added. The mixture was stirred at 8000 r / min for 10 min using a high-speed stirrer. The stirred mixed solution was placed in a supercritical reactor for reaction. During the reaction, carbon dioxide gas was protected, the temperature in the reactor was maintained at 20°C, the pressure was set to 40MPa, and the reaction was carried out for 3h to obtain a supercritical modified boron nitride nanotube thermal conductive filler. The supercritical modified boron nitride nanotube thermal conductive filler was mixed into the acrylic adhesive at a volume fraction of 30% and stirred at a high speed of 15000r / min for 20min to obtain an adhesive.
[0028] Example 5: A mixed solution of anhydrous ethanol and distilled water with a mass ratio of 9:1 was prepared, and the pH was adjusted to 5 with acetic acid. 15g of silane coupling agent (KH560) was placed in the mixed solution for hydrolysis for 1h. Then the mixed solution and 1g of boron nitride nanotubes with a length of 15μm and a diameter of 100nm were added to a supercritical reactor for reaction. During the reaction, carbon dioxide gas was protected, the temperature in the reactor was maintained at 40°C, the pressure was set to 20MPa, and the reaction was carried out for 2h. After the reaction was completed, the product was taken out and washed with ethanol 3 times, and dried in an oven at 60°C to obtain supercritical modified boron nitride nanotubes using silane coupling agent.
[0029] 25g of acrylic resin was dissolved in butyl acrylate solvent, and then 1g of supercritical modified boron nitride nanotubes was added. The mixture was stirred at 8000 r / min for 10 min using a high-speed stirrer. The stirred mixed solution was placed in a supercritical reactor for reaction. During the reaction, carbon dioxide gas was protected, the temperature in the reactor was maintained at 70°C, the pressure was set to 10MPa, and the reaction was carried out for 1h to obtain a supercritical modified boron nitride nanotube thermal conductive filler. The supercritical modified boron nitride nanotube thermal conductive filler was mixed into the acrylic adhesive at a volume fraction of 30% and stirred at a high speed of 15000r / min for 20min to obtain an adhesive.
[0030] Example 6: A mixed solution of anhydrous ethanol and distilled water with a mass ratio of 9:1 was prepared, and the pH was adjusted to 5 with acetic acid. 10g of silane coupling agent (KH560) was placed in the mixed solution for hydrolysis for 1h. Then the mixed solution and 1g of boron nitride nanotubes with a length of 15μm and a diameter of 100nm were added to a supercritical reactor for reaction. During the reaction, carbon dioxide gas was protected, the temperature in the reactor was maintained at 40°C, the pressure was set to 20MPa, and the reaction was carried out for 2h. After the reaction was completed, the product was taken out and washed with ethanol 3 times, and dried in an oven at 60°C to obtain supercritical modified boron nitride nanotubes using silane coupling agent.
[0031] 25g of acrylic resin was dissolved in butyl acrylate solvent, and then 1g of supercritical modified boron nitride nanotubes was added. The mixture was stirred at 8000 r / min for 10 min using a high-speed stirrer. The stirred mixed solution was placed in a supercritical reactor for reaction. During the reaction, carbon dioxide gas was protected, the temperature in the reactor was maintained at 50°C, the pressure was set to 30MPa, and the reaction was carried out for 1.5h to obtain a supercritical modified boron nitride nanotube thermal conductive filler. The supercritical modified boron nitride nanotube thermal conductive filler was mixed into the acrylic adhesive at a volume fraction of 30% and stirred at a high speed of 15000r / min for 20min to obtain an adhesive.
[0032] Example 7, a mixed solution of anhydrous ethanol and distilled water with a mass ratio of 9:1 was prepared, and the pH was adjusted to 5 with acetic acid. 20g of silane coupling agent (KH560) was put into the mixed solution for hydrolysis for 1h. Then the mixed solution and 1g of boron nitride nanotubes with a length of 15μm and a diameter of 100nm were added to a supercritical reactor for reaction. During the reaction, carbon dioxide gas was protected, the temperature in the reactor was maintained at 40°C, the pressure was set to 20MPa, and the reaction was carried out for 2h. After the reaction was completed, the product was taken out and washed with ethanol 3 times, and dried in an oven at 60°C to obtain supercritical modified boron nitride nanotubes using silane coupling agent.
[0033] 25g of acrylic resin was dissolved in butyl acrylate solvent, and then 1g of supercritical modified boron nitride nanotubes was added. The mixture was stirred at 8000 r / min for 10 min using a high-speed stirrer. The stirred mixed solution was placed in a supercritical reactor for reaction. During the reaction, carbon dioxide gas was protected, the temperature in the reactor was maintained at 50°C, the pressure was set to 30MPa, and the reaction was carried out for 1.5h to obtain a supercritical modified boron nitride nanotube thermal conductive filler. The supercritical modified boron nitride nanotube thermal conductive filler was mixed into the acrylic adhesive at a volume fraction of 30% and stirred at a high speed of 15000r / min for 20min to obtain an adhesive.
[0034] Example 8, a mixed solution of anhydrous ethanol and distilled water with a mass ratio of 9:1 was prepared, and the pH was adjusted to 5 with acetic acid. 15g of silane coupling agent (KH560) was put into the mixed solution for hydrolysis for 1h. Then the mixed solution and 1g of boron nitride nanotubes with a length of 15μm and a diameter of 100nm were added to a supercritical reactor for reaction. During the reaction, carbon dioxide gas was protected, the temperature in the reactor was maintained at 40°C, the pressure was set to 20MPa, and the reaction was carried out for 2h. After the reaction was completed, the product was taken out and washed with ethanol 3 times, and dried in an oven at 60°C to obtain supercritical modified boron nitride nanotubes using silane coupling agent.
[0035] 10g of acrylic resin was dissolved in butyl acrylate solvent, and then 1g of supercritical modified boron nitride nanotubes was added. The mixture was stirred at 8000 r / min for 10min using a high-speed stirrer. The stirred mixed solution was placed in a supercritical reactor for reaction. During the reaction, carbon dioxide gas was protected, the temperature in the reactor was maintained at 50°C, the pressure was set to 30MPa, and the reaction was carried out for 1.5h to obtain a supercritical modified boron nitride nanotube thermal conductive filler. The supercritical modified boron nitride nanotube thermal conductive filler was mixed into the acrylic adhesive at a volume fraction of 30% and stirred at a high speed of 15000r / min for 20min to obtain an adhesive.
[0036] Example 9, a mixed solution of anhydrous ethanol and distilled water with a mass ratio of 9:1 was prepared, and the pH was adjusted to 5 with acetic acid. 15g of silane coupling agent (KH560) was put into the mixed solution for hydrolysis for 1h. Then the mixed solution and 1g of boron nitride nanotubes with a length of 15μm and a diameter of 100nm were added to a supercritical reactor for reaction. During the reaction, carbon dioxide gas was protected, the temperature in the reactor was maintained at 40°C, the pressure was set to 20MPa, and the reaction was carried out for 2h. After the reaction was completed, the product was taken out and washed with ethanol 3 times, and dried in an oven at 60°C to obtain supercritical modified boron nitride nanotubes using silane coupling agent.
[0037] 40g of acrylic resin was dissolved in butyl acrylate solvent, and then 1g of supercritical modified boron nitride nanotubes was added. The mixture was stirred at 8000 r / min for 10min using a high-speed stirrer. The stirred mixed solution was placed in a supercritical reactor for reaction. During the reaction, carbon dioxide gas was protected, the temperature in the reactor was maintained at 50°C, the pressure was set to 30MPa, and the reaction was carried out for 1.5h to obtain a supercritical modified boron nitride nanotube thermal conductive filler. The supercritical modified boron nitride nanotube thermal conductive filler was mixed into the acrylic adhesive at a volume fraction of 30% and stirred at a high speed of 15000r / min for 20min to obtain an adhesive.
[0038] Example 10: A mixed solution of anhydrous ethanol and distilled water with a mass ratio of 9:1 was prepared, and the pH was adjusted to 5 with acetic acid. 15g of silane coupling agent (KH550) was placed in the mixed solution for hydrolysis for 1h. Then the mixed solution and 1g of boron nitride nanotubes with a length of 10μm and a diameter of 50nm were added to a supercritical reactor for reaction. During the reaction, carbon dioxide gas was protected, the temperature in the reactor was maintained at 40°C, the pressure was set to 20MPa, and the reaction was carried out for 2h. After the reaction was completed, the product was taken out and washed with ethanol 3 times, and dried in an oven at 60°C to obtain supercritical modified boron nitride nanotubes using silane coupling agent.
[0039] 25g of acrylic resin was dissolved in butyl acrylate solvent, and then 1g of supercritical modified boron nitride nanotubes was added. The mixture was stirred at 8000 r / min for 10 min using a high-speed stirrer. The stirred mixed solution was placed in a supercritical reactor for reaction. During the reaction, carbon dioxide gas was protected, the temperature in the reactor was maintained at 50°C, the pressure was set to 30MPa, and the reaction was carried out for 1.5h to obtain a supercritical modified boron nitride nanotube thermal conductive filler. The supercritical modified boron nitride nanotube thermal conductive filler was mixed into the acrylic adhesive at a volume fraction of 30% and stirred at a high speed of 15000r / min for 20min to obtain an adhesive.
[0040] Example 11, a mixed solution of anhydrous ethanol and distilled water with a mass ratio of 9:1 was prepared, and the pH was adjusted to 5 with acetic acid. 15g of silane coupling agent (KH570) was put into the mixed solution for hydrolysis for 1h. Then the mixed solution and 1g of boron nitride nanotubes with a length of 20μm and a diameter of 200nm were added to a supercritical reactor for reaction. During the reaction, carbon dioxide gas was protected, the temperature in the reactor was maintained at 40°C, the pressure was set to 20MPa, and the reaction was carried out for 2h. After the reaction was completed, the product was taken out and washed with ethanol 3 times, and dried in an oven at 60°C to obtain supercritical modified boron nitride nanotubes using silane coupling agent.
[0041] 25g of acrylic resin was dissolved in butyl acrylate solvent, and then 1g of supercritical modified boron nitride nanotubes was added. The mixture was stirred at 8000 r / min for 10 min using a high-speed stirrer. The stirred mixed solution was placed in a supercritical reactor for reaction. During the reaction, carbon dioxide gas was protected, the temperature in the reactor was maintained at 50°C, the pressure was set to 30MPa, and the reaction was carried out for 1.5h to obtain a supercritical modified boron nitride nanotube thermal conductive filler. The supercritical modified boron nitride nanotube thermal conductive filler was mixed into the acrylic adhesive at a volume fraction of 30% and stirred at a high speed of 15000r / min for 20min to obtain an adhesive.
[0042] Example 12: A mixed solution of anhydrous ethanol and distilled water with a mass ratio of 9:1 was prepared, and the pH was adjusted to 5 with acetic acid. 15g of silane coupling agent (KH560) was placed in the mixed solution for hydrolysis for 1h. Then the mixed solution and 1g of boron nitride nanotubes with a length of 15μm and a diameter of 100nm were added to a supercritical reactor for reaction. During the reaction, carbon dioxide gas was protected, the temperature in the reactor was maintained at 40°C, the pressure was set to 20MPa, and the reaction was carried out for 2h. After the reaction was completed, the product was taken out and washed with ethanol 3 times, and dried in an oven at 60°C to obtain supercritical modified boron nitride nanotubes using silane coupling agent.
[0043] 25g of acrylic resin was dissolved in butyl acrylate solvent, and then 1g of supercritical modified boron nitride nanotubes was added. The mixture was stirred at 6000 r / min for 20min using a high-speed stirrer. The stirred mixed solution was placed in a supercritical reactor for reaction. During the reaction, carbon dioxide gas was protected, the temperature in the reactor was maintained at 50°C, the pressure was set to 30MPa, and the reaction was carried out for 1.5h to obtain a supercritical modified boron nitride nanotube thermal conductive filler. The supercritical modified boron nitride nanotube thermal conductive filler was mixed into the acrylic adhesive at a volume fraction of 15% and stirred at a high speed of 12000r / min for 10min to obtain an adhesive.
[0044] Example 13, a mixed solution of anhydrous ethanol and distilled water with a mass ratio of 9:1 was prepared, and the pH was adjusted to 5 with acetic acid. 15g of silane coupling agent (KH560) was put into the mixed solution for hydrolysis for 1h. Then the mixed solution and 1g of boron nitride nanotubes with a length of 15μm and a diameter of 100nm were added to a supercritical reactor for reaction. During the reaction, carbon dioxide gas was protected, the temperature in the reactor was maintained at 40°C, the pressure was set to 20MPa, and the reaction was carried out for 2h. After the reaction was completed, the product was taken out and washed with ethanol 3 times, and dried in an oven at 60°C to obtain supercritical modified boron nitride nanotubes using silane coupling agent.
[0045] 25g of acrylic resin was dissolved in butyl acrylate solvent, and then 1g of supercritical modified boron nitride nanotubes was added. The mixture was stirred at 10000 r / min for 5min using a high-speed stirrer. The stirred mixed solution was placed in a supercritical reactor for reaction. During the reaction, carbon dioxide gas was protected, the temperature in the reactor was maintained at 50°C, the pressure was set to 30MPa, and the reaction was carried out for 1.5h to obtain a supercritical modified boron nitride nanotube thermal conductive filler. The supercritical modified boron nitride nanotube thermal conductive filler was mixed into the acrylic adhesive at a volume fraction of 45% and stirred at a high speed of 14000r / min for 15min to obtain an adhesive.
[0046] Comparative Example 1 is a pure acrylic adhesive.
[0047] Comparative Example 2 uses unmodified boron nitride nanotubes with a length of 15 μm and a diameter of 100 nm to mix into acrylic adhesive at a volume fraction of 30%, and stir at high speed for 10 minutes at a stirring speed of 10000 r / min to prepare a thermally conductive adhesive.
[0048] Comparative Example 3 A mixed solution of anhydrous ethanol and distilled water with a mass ratio of 9:1 was prepared, and the pH was adjusted to 5 with acetic acid. 15g of silane coupling agent (KH560) was put into the mixed solution for hydrolysis for 1h. Then the mixed solution was reacted with 1g of boron nitride nanotubes with a length of 15μm and a diameter of 100nm at 60°C under normal pressure to obtain a modified boron nitride nanotube thermal conductive filler, and then the modified boron nitride nanotube thermal conductive filler was mixed into the acrylic adhesive at a volume fraction of 30% and stirred at high speed for 10min at a stirring speed of 10000r / min to obtain a thermal conductive adhesive.
[0049] In comparative example 4, the supercritical modified boron nitride nanotubes obtained in Example 1 were mixed into an acrylic adhesive at a volume fraction of 30%, and stirred at a high speed of 15000 r / min for 20 min to prepare an adhesive.
[0050] In comparative example 5, 25 g of acrylic resin was dissolved in butyl acrylate solvent, and then 1 g of supercritical modified boron nitride nanotubes obtained in Example 1 was added, and stirred at 8000 r / min for 10 min using a high-speed stirrer. The stirred mixed solution was placed in a reactor at 50° C. under normal pressure to react to obtain a thermally conductive filler, and the thermally conductive filler was mixed into the acrylic adhesive at a volume fraction of 30%, and stirred at a high speed of 15000 r / min for 20 min to obtain an adhesive.
[0051] The thermal conductive paste and pure boron nitride nanotubes obtained in Example 1 were subjected to filler thermogravimetric analysis (TGA) to detect the grafting amount of acrylic acid molecules on the surface of the modified boron nitride nanotubes. Figure 1 As shown, the unmodified BN nanotubes (1) have high thermal stability up to 800 o C, only about 0.43% weight loss was caused by the evaporation of water on the surface of BN nanotubes. o C, the modified boron nitride nanotubes (2) of Example 1 began to lose weight. When the temperature was raised to 500 o C, the weight loss reaches a stable level. At this time, the modified boron nitride nanotubes have a total weight loss of about 10%, which is mainly caused by the thermal decomposition of the acrylic acid molecules grafted on the surface of the modified boron nitride nanotubes. It can be inferred that the grafting rate of acrylic acid on the surface of the boron nitride nanotubes after supercritical modification is about 10%.
[0052] Please combine again Figure 2 As shown in the figure, the left picture shows the state of ungrafted boron nitride nanotubes in acrylic emulsion after 48 hours of standing, and the material has obvious stratification and sedimentation. The right picture shows the state of supercritically modified boron nitride nanotubes in acrylic emulsion after 48 hours of standing. It can be seen that the filler can be stably dispersed in the solution, indicating that the supercritically modified boron nitride nanotubes have better dispersibility in acrylic adhesives.
[0053] The thermal conductivity of the above-mentioned embodiments and comparative examples was tested. Sample preparation: The obtained adhesive was coated on release paper with a coater, and then placed in a 90°C blast drying oven for 10 minutes to remove residual monomers and solvents, and a test sample with a thickness of 1 mm was prepared. The thermal conductivity test method was carried out in accordance with ASTM E1461 standard, and the results are shown in Table 1.
[0054] Table 1 shows the thermal conductivity test results of various embodiments and comparative examples.
[0055]
[0056] High thermal conductivity adhesives are mostly used in electronic equipment, LED, electronic packaging and other fields, and they must also have excellent electrical insulation properties. The volume resistivity of acrylic adhesives was tested by a high resistance meter to analyze the electrical insulation properties of acrylic thermal conductive tapes. The volume resistivity test was carried out in accordance with GB / T 1410-1989, and the result of Example 1 was 15×10 14 ·cm, the remaining embodiments also meet the critical standard of electrical insulators (10 9 ·cm).
Claims
1. A method for preparing a supercritical modified boron nitride nanotube thermal conductive filler, characterized in that: The invention comprises the following steps: adding the hydrolyzed silane coupling agent and the boron nitride nanotubes together to a supercritical reactor for reaction, wherein the reaction process is protected by carbon dioxide gas, the temperature is maintained at 40-60°C, the pressure is set to 8-30MPa, and the normal pressure is restored within 5 seconds after the reaction is completed to obtain supercritical modified boron nitride nanotubes; adding the supercritical modified boron nitride nanotubes to an acrylic acid monomer solution and stirring to obtain a mixed solution; placing the mixed solution in a supercritical reactor for reaction, wherein the reaction process is protected by carbon dioxide gas, the temperature is maintained at 50-70°C, the pressure is set to 10-40MPa, and the supercritical modified boron nitride nanotube thermal conductive filler is obtained after the reaction is completed; the silane coupling agent is one of KH550 and KH570; the acrylic acid monomer solution is prepared by dissolving acrylic acid monomer in butyl acrylate solvent; and the mass ratio of the supercritical modified boron nitride nanotubes to the acrylic acid monomer solution in the mixed solution is 1:25-40 based on the supercritical modified boron nitride nanotubes to the acrylic acid monomer.
2. The method for preparing the supercritical modified boron nitride nanotube thermal conductive filler according to claim 1, characterized in that: The mass ratio of the boron nitride nanotubes to the hydrolyzate of the silane coupling agent is 1:5-30 based on the boron nitride nanotubes and the silane coupling agent.
3. The method for preparing the supercritical modified boron nitride nanotube thermal conductive filler according to claim 1, characterized in that: The boron nitride nanotube has a length of 10 to 20 μm and a diameter of 50 to 200 nm.
4. The method for preparing the supercritical modified boron nitride nanotube thermal conductive filler according to claim 1, characterized in that: The silane coupling agent is hydrolyzed with an ethanol aqueous solution.
5. A method for preparing an adhesive, characterized in that: The supercritical modified boron nitride nanotube thermal conductive filler prepared by the preparation method of the supercritical modified boron nitride nanotube thermal conductive filler according to any one of claims 1 to 4 is mixed into an acrylic adhesive and stirred to prepare the supercritical modified boron nitride nanotube thermal conductive filler.
6. The method for preparing the adhesive according to claim 5, characterized in that: The volume fraction of the supercritical modified boron nitride nanotube thermal conductive filler in the acrylic adhesive is 15% to 40%.
7. The method for preparing the adhesive according to claim 5, characterized in that: The supercritical modified boron nitride nanotube thermal conductive filler is mixed into the acrylic adhesive and stirred at 12000-15000 r / min for 10-20 minutes.
Citation Information
Patent Citations
Manufacturing method of heat conduction material, heat conduction material and heat conduction bracket
CN113801467A
Supercritical fluid pressure sensitive adhesive polymers and their preparation
US20020035225A1